Reshaping the copyright law for the protection of works in the digital era / Lim Heng Gee - Lim, Heng Gee (Faculty of Administratron and Law, 2001)
In recent years there has been a flurry of legislative activities in relation to intellectual property laws. The resulting amendments and introduction of new rights were carried out mainly to ensure that Malaysia is in compliance with her obligations under the World Trade Organisation's Agreement on Trade-Related Aspects of Intellectual Property Rights (WTO-TRIPS Agreement).1 Among the new laws promulgated were the Trade Marks (Amendment) Act 1994, Industrial Designs Act 1996, Copyright (Amendment) Act 1997, Copyright (Amendment) Act 2000, Patents (Amendment) Act 2000, Trade Marks (Amendment) Act 2000, Geographical Indications Act 2000, the Optical Discs Act 2000 and the Layout Designs (Topographies) of Integrated Circuits Act 2000. This article discusses only the relevant amendments to the Copyright Act 1987 (the Act) which have impact on how works in the digital era could be properly protected. The main vehicle for these changes is the Copyright (Amendment Act) 1997 (the 1997 Amendment Act). Therefore, discussion in this article will focus mainly on the provisions of the 1997 Amendment Act. Where relevant, reference will also be made to the Copyright (Amendment) Act 2000.